eXceptional and INcluded : tuawāhine in waka ama : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Mātauranga Māori at Massey University, Palmerston North, New Zealand - Nuku, Ronalda (Massey University, 2023)
This thesis explores the lived experiences of five exceptional wāhine with a passion for waka ama. It draws on a Māori lens to understand the experiences of tuawāhine living with differing abilities or impairments, participating in a sporting context that is inclusive. The research is centred on kaupapa Māori and tikanga principles of whanaungatanga and manaakitanga. The inclusive methodology, Participatory Action Research approach, was selected for this rangahau. It is the ideal tool to empower groups that live on the borders because it facilitates, in a genuine and authentic way, the expression of marginalised perspectives (Smith, 2021). The rangahau captured the voices of the tuawāhine and exposed ngā piki me ngā heke, the triumphs and the setbacks. The ups of being included in sport that connects them culturally and relationally, the benefits that have uplifted the wairua and provided wellness to their hauora and a platform for social justice. The downs expressed were the control from political ideologies and western paradigms that continue to oppress them. All of those do not detract however from the tuawāhine enjoying life to its fullest. Their zest is inspiring and their laughter is infectious. Waka ama has been the mechanism for these tuawāhine, in our communities to be more visible. It has provided opportunities for people living with differing abilities to participate in sport, which has in turn created exposure, both are important in creating a society that is accessible to all.
Keywords: Māori Masters Thesis; 451019 Ngā hākinakina me te korikori tinana o te Māori (Māori sport and physical activity)